The Role of Mrisho Mpoto's Songs in Developing Oral Literature. Issue 3 (2nd October 2019) - Makhulo, Evans
ABSTRACT: This paper investigates the contribution of Mrisho Mpoto's songs in developing oral literature. It does so by examining the role of oral literature and evaluating the extent to which his songs advance the said role. Furthermore, we propose to show how the language used by Mpoto is rich in stylistic devices and in the lexical repertoire employed in oral literature. We analyse his two songs: ' Salamu Zangu Mjomba ' ('My Message, Uncle') and ' Asanteni kwa Kuja ' ('Thanks for Coming'). We argue that these songs enrich and advance oral literature. Finally, we conclude that these songs are rich in stylistic devices employed in oral literature and therefore an important reservoir in oral literature.